The Potential of Coordinated Gravitational-wave Follow-up for Improving Kilonova Detection Prospects: Lessons from GW190425 - Ido Keinan; Iair Arcavi (The Astrophysical Journal)
The discovery of a kilonova associated with the GW170817 binary neutron star (BNS) merger had far-reaching implications for our understanding of several open questions in physics and astrophysics. Unfortunately, since then, only one robust BNS merger has been detected through gravitational waves, GW190425, and no electromagnetic (EM) counterpart was identified for it following an uncoordinated search. In order to estimate the potential difference that coordinated follow-up could make for future events, we analyze all reported EM follow-up observations of GW190425. We find that even for a large gravitational-wave localization uncertainty, such as this one, most of the 90% probability region can be covered within hours with a coordinated search, given the observational resources expended in this case by the community. However, more than 5 days after the GW190425 merger, its uncoordinated search covered only 50% of the probability, with some areas observed over 100 times, and some never observed. According to some models, the GW190425 kilonova could have been detected, despite the larger distance and higher component masses compared to GW170817. These results emphasize that coordinated follow-up of gravitational-wave events can, in principle, significantly improve both the chances of finding EM counterparts, and the time it takes to do so, compared to uncoordinated searches.